Side Effects of Hormonal Contraception of Patients in the Family Planning of Centre University Hospital of Mother and Child Lagoon, Cotonou (Benin)... - TONATO EPSE BAGNAN, JOSIANE ANGÉLINA ADJOUA; ABOUBAKAR, MOUFALILOU; TOGNIFODE, Véronique; LOKOSSOU, Mègnissè Sèna H. S.; PERRIN, RENÉ-XAVIER (My University, 2017)
Objective: To take a census of side effects related to the use of hormonal contraception reported by the women received in the Family Planning (FP) Service of CHU-MEL. Patients and methods: It was a cross-sectional prospective study which was carried out in the family planning service ofCHU-MEL in Cotonouover a three-month period from June 1st to August 31st, 2016. Results: 303 women were involved in this survey. The average age was 33 years (extremes of 15 and 49 years).Side effects were vaginal bleeding apart from the menses (37.2%) amenorrhea (32%) and weight increase (27.3%). The reasons for abandonment of hormonal contraceptionwere amenorrhea (13%), weight gain (11%), pelvic pain (0.07), nausea (0.05%) and bleeding (0.04). Conclusion: Hormonal contraception has many side effects. Some of them are well known by patients. They influence compliance with treatment. Their management is not always optimal and leads to abandonment.
Keywords: Hormonal contraception; Side effects; Cotonou